METHODS FOR PROFESSIONAL IMAGE FORMATION IN FUTURE EDUCATIONAL MANAGERS DURING THEIR MASTER’S TRAINING - Титаренко, Анастасія (SWorldJournal, 2023)
The article reveals the problem of professional image formation in future education managers during their master’s training. it has been found that in the conditions of competition and constant changes in the educational sphere, the formed professional i